On type systems for object-oriented database programming languages. - Leontiev, Yuri (ACM computing surveys.)
The concept of an object-oriented database programming language (OODBPL) is appealing because it has the potential of combining the advantages of object orientation and database programming to yield a powerful and universal programming language design. A uniform and consistent combination of object orientation and database programming, however, is not straightforward. Since one of the main components of an object-oriented programming language is its type system, one of the first problems that arises during an OODBPL design is related to the development of a uniform, consistent, and theoretically sound type system that is sufficiently expressive to satisfy the combined needs of object orientation and database programming.The purpose of this article is to answer two questions: "What are the requirements that a modern type system for an object-oriented database programming language should satisfy?" and "Are there any type systems developed to-date that satisfy these requirements?". In order to answer the first question, we compile the set of requirements that an OODBPL type system should satisfy. We then use this set of requirements to evaluate more than 30 existing type systems. The result of this extensive analysis shows that while each of the requirements is satisfied by at least one type system, no type system satisfies all of them. It also enables identification of the mechanisms that lie behind the strengths and weaknesses of the current type systems.